Identifying Factors Associated with the Occurrence of Marital Infidelity: A Systematic Review - Saeidi Haghi, Solmaz; Madani, Yaser; Salehi, Keyvan; Behpajooh, Ahmad (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to identify and classify the factors associated with the occurrence of marital infidelity based on a systematic review of national and international studies.Methods and Materials: The present study was conducted using a documentary research design and a systematic review approach. Relevant studies were identified through systematic searches of national databases, including IranDoc, the Scientific Information Database (SID), and Civilica, as well as international databases, including Scopus, PsycINFO, and Google Scholar. Keywords such as marital infidelity, extramarital relationships, factors affecting infidelity, and their Persian and English equivalents were used in the search process. After screening titles, abstracts, and full texts according to predefined inclusion and exclusion criteria, 46 eligible studies were selected for final analysis. Data were extracted from the included studies and analyzed through coding and qualitative content analysis to identify recurring themes and categories.Findings: The qualitative synthesis indicated that the factors associated with marital infidelity could be classified into five main components. Individual factors included personality traits and disorders, psychological and emotional conditions, and personal beliefs and attitudes. Relational factors included emotional and communicative quality, sexual and physical functioning, and the structure and history of the marital relationship. Familial factors included developmental background, family patterns, and kinship relationship networks. Socioeconomic factors included occupational and economic contexts, as well as social and cultural pressures. Technological factors included cyberspace, online interactions, and the role of digital technologies in facilitating extramarital relationships.Conclusion: Marital infidelity is a multidimensional phenomenon shaped by the interaction of individual vulnerabilities, relational dynamics, family background, socioeconomic pressures, and technological contexts. Therefore, prevention and intervention programs should adopt an integrative perspective that addresses both personal and contextual determinants of marital relationships.Keywords: Marital infidelity; extramarital relationships; marital satisfaction; psychological factors; systematic review.